2016
DOI: 10.2141/jpsa.0150001
|View full text |Cite
|
Sign up to set email alerts
|

Fructosyl-Valine Orally Administrated to Chickens is Absorbed from Gastrointestinal Tract

Abstract: Amadori products are non-enzymatically formed by binding carbonyl groups and amino groups. Glycated amino acids generated by reacting amino acid and glucose are also in a group of Amadori products of which the transport and metabolism have been investigated mainly in mammals but not in avians. In the present study, therefore, we examined whether dietary fructosyl-valine, which is one of the glycated amino acids, orally administrated to chickens can be incorporated into blood or not. Fructosyl-valine was orally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…2, when fructosyl-valine was administered orally to chicks, the plasma fructosyl-valine concentration increased gradually and reached the highest value 180 min after administration. This is in good agreement with our previous study (Takahashi and Kita, 2016), and these results suggest that fructosyl-valine can be absorbed from gastrointestinal tract and transferred into circulating blood. When administered orally, the plasma half-life of fructosyl-valine in chicks was calculated to be 277 min.…”
Section: Discussionsupporting
confidence: 93%
“…2, when fructosyl-valine was administered orally to chicks, the plasma fructosyl-valine concentration increased gradually and reached the highest value 180 min after administration. This is in good agreement with our previous study (Takahashi and Kita, 2016), and these results suggest that fructosyl-valine can be absorbed from gastrointestinal tract and transferred into circulating blood. When administered orally, the plasma half-life of fructosyl-valine in chicks was calculated to be 277 min.…”
Section: Discussionsupporting
confidence: 93%
“…Previously, we could successfully synthesize Amadori products from glucose and tryptophan, and measured the plasma concentrations of glycated-tryptophan (Kita et al, 2013;Makino et al, 2015). Furthermore, we have been able to synthesize glycated-valine (Takahashi and Kita, 2016). In the present study, therefore, radioactive glycated-tryptophan and -valine were prepared to investigate their incorporation into various chicken embryonic cells.…”
Section: Introductionmentioning
confidence: 94%
“…We have recently established the analytical methods to measure plasma concentrations of tryptophan-Amadori product and PHP-TH β C ( Kita et al , 2013 ; Makino et al , 2015a ) and valine-Amadori products ( Takahashi and Kita, 2016 ). As shown in Table 3 , Amadori products of tryptophan and valine were successfully measured, and the derived results revealed that approximately 60% of tryptophan and 40% of valine were glycated, even when chickens were fed on the control (CP 20%) diet.…”
Section: Discussionmentioning
confidence: 99%